A FEMINIST PERSPECTIVE ON JAY ASHER'S 13 REASONS WHY - Dono Sunardi; Ranty A. Dewi (ELite Journal : International Journal of Education, Language, and Literature, 2022)
This paper focuses on how female objectification, rape culture, and patriarchy are portrayed and represented in Jay Asher's 13 Reasons Why (2007). This paper addresses the following questions: 1) How do male characters objectify Hannah Baker, the female major character in the novel? 2) How do 13 Reasons Why reflect rape culture in American society? 3) How do female objectification and rape culture in the novel represent patriarchy? Therefore, the objectives of this paper are in line with the problems, describing how male characters in the story objectify Hannah Baker, identifying how 13 Reasons Why reflects rape culture in American society, and arguing how female objectification and rape culture in the story represent patriarchy. To do so, theories of female objectification and rape culture are employed. In addition, since this is a descriptive qualitative study, the main instrument is the writers themselves, who read and scrutinize the text in the light of the theories. After exploration, it is found that male characters in the novel objectify Hannah Baker in several cases. There are also evidence of rape culture in American society as represented in the story. To conclude, the writer finds patriarchy as the root of female objectification and rape culture, a vicious circle.